Sea-level rise and resilience in Vietnam and the Asia-Pacific: A synthesis - Hens, Luc; Thinh, Nguyen An; Hanh, Tran Hong; Cuong, Ngo Sy; Lan, Tran Dinh; Thanh, Nguyen Van; Le, Dang Thanh (Vietnam Journal of Earth Sciences, 2018)
Climate change induced sea-level rise (SLR) is on its increase globally. Regionally the lowlands of China, Vietnam, Bangladesh, and islands of the Malaysian, Indonesian and Philippine archipelagos are among the world’s most threatened regions. Sea-level rise has major impacts on the ecosystems and society. It threatens coastal populations, economic activities, and fragile ecosystems as mangroves, coastal salt-marches and wetlands. This paper provides a summary of the current state of knowledge of sea level-rise and its effects on both human and natural ecosystems. The focus is on coastal urban areas and low lying deltas in South-East Asia and Vietnam, as one of the most threatened areas in the world. About 3 mm per year reflects the growing consensus on the average SLR worldwide. The trend speeds up during recent decades. The figures are subject to local, temporal and methodological variation. In Vietnam the average values of 3.3 mm per year during the 1993-2014 period are above the worldwide average. Although a basic conceptual understanding exists that the increasing global frequency of the strongest tropical cyclones is related with the increasing temperature and SLR, this relationship is insufficiently understood. Moreover the precise, complex environmental, economic, social, and health impacts are currently unclear. SLR, storms and changing precipitation patterns increase flood risks, in particular in urban areas. Part of the current scientific debate is on how urban agglomeration can be made more resilient to flood risks. Where originally mainly technical interventions dominated this discussion, it becomes increasingly clear that proactive special planning, flood defense, flood risk mitigation, flood preparation, and flood recovery are important, but costly instruments. Next to the main focus on SLR and its effects on resilience, the paper reviews main SLR associated impacts: Floods and inundation, salinization, shoreline change, and effects on mangroves and wetlands. The hazards of SLR related floods increase fastest in urban areas. This is related with both the increasing surface major cities are expected to occupy during the decades to come and the increasing coastal population. In particular Asia and its megacities in the southern part of the continent are increasingly at risk. The discussion points to complexity, inter-disciplinarity, and the related uncertainty, as core characteristics. An integrated combination of mitigation, adaptation and resilience measures is currently considered as the most indicated way to resist SLR today and in the near future.References Aerts J.C.J.H., Hassan A., Savenije H.H.G., Khan M.F., 2000. Using GIS tools and rapid assessment techniques for determining salt intrusion: Stream a river basin management instrument. Physics and Chemistry of the Earth, Part B: Hydrology, Oceans and Atmosphere, 25, 265-273. Doi: 10.1016/S1464-1909(00)00014-9. Alongi D.M., 2002. Present state and future of the world’s mangrove forests. Environmental Conservation, 29, 331-349. Doi: 10.1017/S0376892902000231 Alongi D.M., 2015. The impact of climate change on mangrove forests. Curr. Clim. Change Rep., 1, 30-39. Doi: 10.1007/s404641-015-0002-x. Anderson F., Al-Thani N., 2016. Effect of sea level rise and groundwater withdrawal on seawater intrusion in the Gulf Coast aquifer: Implications for agriculture. Journal of Geoscience and Environment Protection, 4, 116-124. Doi: 10.4236/gep.2016.44015. Anguelovski I., Chu E., Carmin J., 2014. Variations in approaches to urban climate adaptation: Experiences and experimentation from the global South. Global Environmental Change, 27, 156-167.  Doi: 10.1016/j.gloenvcha.2014.05.010. Arustienè J., Kriukaitè J., Satkunas J., Gregorauskas M., 2013. Climate change and groundwater - From modelling to some adaptation means in example of Klaipèda region, Lithuania. In: Climate change adaptation in practice. P. Schmidt-Thomé, J. Klein Eds. John Wiley and Sons Ltd., Chichester, UK., 157-169. Bamber J.L., Aspinall W.P., Cooke R.M., 2016. A commentary on “how to interpret expert judgement assessments of twenty-first century sea-level rise” by Hylke de Vries and Roderik S.W. Van de Wal. Climatic Change, 137, 321-328. Doi: 10.1007/s10584-016-1672-7. Barnes C., 2014. Coastal population vulnerability to sea level rise and tropical cyclone intensification under global warming. BSc-thesis. Department of Geography, University of Lethbridge, Alberta Canada. Be T.T., Sinh B.T., Miller F., 2007. Challenges to sustainable development in the Mekong Delta: Regional and national policy issues and research needs. The Sustainable Mekong Research Network, Bangkok, Thailand, 1-210. Bellard C., Leclerc C., Courchamp F., 2014. Impact of sea level rise on 10 insular biodiversity hotspots. Global Ecology and Biogeography, 23, 203-212. Doi: 10.1111/geb.12093. Berg H., Söderholm A.E., Sönderström A.S., Nguyen Thanh Tam, 2017. Recognizing wetland ecosystem services for sustainable rice farming in the Mekong delta, Vietnam. Sustainability Science, 12, 137-154. Doi: 10.1007/s11625-016-0409-x. Bilskie M.V., Hagen S.C., Medeiros S.C., Passeri D.L., 2014. Dynamics of sea level rise and coastal flooding on a changing landscape. Geophysical Research Letters, 41, 927-934. Doi: 10.1002/2013GL058759. Binh T.N.K.D., Vromant N., Hung N.T., Hens L., Boon E.K., 2005. Land cover changes between 1968 and 2003 in Cai Nuoc, Ca Mau penisula, Vietnam. Environment, Development and Sustainability, 7, 519-536. Doi: 10.1007/s10668-004-6001-z. Blankespoor B., Dasgupta S., Laplante B., 2014. Sea-level rise and coastal wetlands. Ambio, 43, 996- 005.Doi: 10.1007/s13280-014-0500-4. Brockway R., Bowers D., Hoguane A., Dove V., Vassele V., 2006. A note on salt intrusion in funnel shaped estuaries: Application to the Incomati estuary, Mozambique.Estuarine, Coastal and Shelf Science, 66, 1-5. Doi: 10.1016/j.ecss.2005.07.014. Cannaby H., Palmer M.D., Howard T., Bricheno L., Calvert D., Krijnen J., Wood R., Tinker J., Bunney C., Harle J., Saulter A., O’Neill C., Bellingham C., Lowe J., 2015. Projected sea level rise and changes in extreme storm surge and wave events during the 21st century in the region of Singapore. Ocean Sci. Discuss, 12, 2955-3001. Doi: 10.5194/osd-12-2955-2015. Carraro C., Favero A., Massetti E., 2012. Investment in public finance in a green, low carbon economy. Energy Economics, 34, S15-S18. Castan-Broto V., Bulkeley H., 2013. A survey ofurban climate change experiments in 100 cities. Global Environmental Change, 23, 92-102. Doi: 10.1016/j.gloenvcha.2012.07.005. Cazenave A., Le Cozannet G., 2014. Sea level rise and its coastal impacts. GeoHealth, 2, 15-34. Doi: 10.1002/2013EF000188. Chu M.L., Guzman J.A., Munoz-Carpena R., Kiker G.A., Linkov I., 2014. A simplified approach for simulating changes in beach habitat due to the combined effects of long-term sea level rise, storm erosion and nourishment. Environmental modelling and software, 52, 111-120. Doi.org/10.1016/j.envcsoft.2013.10.020. Church J.A. et al., 2013. Sea level change. In: Climate change 2013: The physical science basis. Contribution of working group I to the fifth assessment report of Intergovernmental Panel on Climate Change. Eds: Stocker T.F., Qin D., Plattner G.-K., Tignor M., Allen S.K., Boschung J., Nauels A., Xia Y., Bex V., Midgley P.M., Cambridge University Press, Cambridge, UK. Connell J., 2016. Last days of the Carteret Islands? Climate change, livelihoods and migration on coral atolls. Asia Pacific Viewpoint, 57, 3-15. Doi: 10.1111/apv.12118. Dasgupta S., Laplante B., Meisner C., Wheeler, Yan J., 2009. The impact of sea level rise on developing countries: A comparative analysis. Climatic Change, 93, 379-388. Doi: 10.1007/s 10584-008-9499-5. Delbeke J., Vis P., 2015. EU climate policy explained, 136p. Routledge, Oxon, UK. DiGeorgio M., 2015. Bargaining with disaster: Flooding, climate change, and urban growth ambitions in QuyNhon, Vietnam. Public Affairs, 88, 577-597. Doi: 10.5509/2015883577. Do Minh Duc, Yasuhara K., Nguyen Manh Hieu, 2015. Enhancement of coastal protection under the context of climate change: A case study of Hai Hau coast, Vietnam. Proceedings of the 10th Asian Regional Conference of IAEG, 1-8. Do Minh Duc, Yasuhara K., Nguyen Manh Hieu, Lan Nguyen Chau, 2017. Climate change impacts on a large-scale erosion coast of Hai Hau district, Vietnam and the adaptation. Journal of Coastal Conservation, 21, 47-62. Donner S.D., Webber S., 2014. Obstacles to climate change adaptation decisions: A case study of sea level rise; and coastal protection measures in Kiribati. Sustainability Science, 9, 331-345. Doi: 10.1007/s11625-014-0242-z. Driessen P.P.J., Hegger D.L.T., Bakker M.H.N., Van Renswick H.F.M.W., Kundzewicz Z.W., 2016. Toward more resilient flood risk governance. Ecology and Society, 21, 53-61. Doi: 10.5751/ES-08921-210453. Duangyiwa C., Yu D., Wilby R., Aobpaet A., 2015. Coastal flood risks in the Bangkok Metropolitan region, Thailand: Combined impacts on land subsidence, sea level rise and storm surge. American Geophysical Union, Fall meeting 2015, abstract#NH33C-1927. Duarte C.M., Losada I.J., Hendriks I.E., Mazarrasa I., Marba N., 2013. The role of coastal plant communities for climate change mitigation and adaptation. Nature Climate Change, 3, 961-968. Doi: 10.1038/nclimate1970. Erban L.E., Gorelick S.M., Zebker H.A., 2014. Groundwater extraction, land subsidence, and sea-level rise in the Mekong Delta, Vietnam. Environmental Research Letters, 9, 1-20. Doi: 10.1088/1748-9326/9/8/084010. FAO - Food and Agriculture Organisation, 2007.The world’s mangroves 1980-2005. FAO Forestry Paper, 153, Rome, Italy. Farbotko C., 2010. Wishful sinking: Disappearing islands, climate refugees and cosmopolitan experimentation. Asia Pacific Viewpoint, 51, 47-60. Doi: 10.1111/j.1467-8373.2010.001413.x. Goltermann D., Ujeyl G., Pasche E., 2008. Making coastal cities flood resilient in the era of climate change. Proceedings of the 4th International Symposium on flood defense: Managing flood risk, reliability and vulnerability, 148-1-148-11. Toronto, Canada. Gong W., Shen J., 2011. The response of salt intrusion to changes in river discharge and tidal mixing during the dry season in the Modaomen Estuary, China.Continental Shelf Research, 31, 769-788. Doi: 10.1016/j.csr.2011.01.011. Gosian L., 2014. Protect the world’s deltas. Nature, 516, 31-34. Graham S., Barnett J., Fincher R., Mortreux C., Hurlimann A., 2015. Towards fair outcomes in adaptation to sea-level rise. Climatic Change, 130, 411-424. Doi: 10.1007/s10584-014-1171-7. COASTRES-D-12-00175.1. Güneralp B., Güneralp I., Liu Y., 2015. Changing global patterns of urban expoàsure to flood and drought hazards. Global Environmental Change, 31, 217-225. Doi: 10.1016/j.gloenvcha.2015.01.002. Hallegatte S., Green C., Nicholls R.J., Corfee-Morlot J., 2013. Future flood losses in major coastal cities. Nature Climate Change, 3, 802-806. Doi: 10.1038/nclimate1979. Hamlington B.D., Strassburg M.W., Leben R.R., Han W., Nerem R.S., Kim K.-Y., 2014. Uncovering an anthropogenic sea-level rise signal in the Pacific Ocean. Nature Climate Change, 4, 782-785. Doi: 10.1038/nclimate2307. Hashimoto T.R., 2001. Environmental issues and recent infrastructure development in the Mekong Delta: Review, analysis and recommendations with particular reference to large-scale water control projects and the development of coastal areas. Working paper series (Working paper No. 4). Australian Mekong Resource Centre, University of Sydney, Australia, 1-70. Hibbert F.D., Rohling E.J., Dutton A., Williams F.H., Chutcharavan P.M., Zhao C., Tamisiea M.E., 2016. Coral indicators of past sea-level change: A global repository of U-series dated benchmarks. Quaternary Science Reviews, 145, 1-56. Doi: 10.1016/j.quascirev.2016.04.019. Hinkel J., Lincke D., Vafeidis A., Perrette M., Nicholls R.J., Tol R.S.J., Mazeion B., Fettweis X., Ionescu C., Levermann A., 2014. Coastal flood damage and adaptation costs under 21st century sea-level rise. Proceedings of the National Academy of Sciences, 111, 3292-3297. Doi: 10.1073/pnas.1222469111. Hinkel J., Nicholls R.J., Tol R.S.J., Wang Z.B., Hamilton J.M., Boot G., Vafeidis A.T., McFadden L., Ganapolski A., Klei R.J.Y., 2013. A global analysis of erosion of sandy beaches and sea level rise: An application of DIVA. Global and Planetary Change, 111, 150-158. Doi: 10.1016/j.gloplacha.2013.09.002. Huong H.T.L., Pathirana A., 2013. Urbanization and climate change impacts on future urban flooding in Can Tho city, Vietnam. Hydrol. Earth Syst. Sci., 17, 379-394. Doi: 10.5194/hess-17-379-2013. Hurlimann A., Barnett J., Fincher R., Osbaldiston N., Montreux C., Graham S., 2014. Urban planning and sustainable adaptation to sea-level rise. Landscape and Urban Planning, 126, 84-93. Doi: 10.1016/j.landurbplan.2013.12.013. IMHEN-Vietnam Institute of Meteorology, Hydrology and Environment, 2011. Climate change vulnerability and risk assessment study for Ca Mau and KienGiang provinces, Vietnam. Hanoi, Vietnam Institute of Meteorology, Hydrology and Environment (IMHEN), 250p. IMHEN-Vietnam Institute of Meteorology, Hydrology and Environment, Ca Mau PPC, 2011. Climate change impact and adaptation study in The Mekong Delta - Part A: Ca Mau Atlas. Hanoi, Vietnam: Institute of Meteorology, Hydrology and Environment (IMHEN), 48p. IPCC-Intergovernmental Panel on Climate Change, 2014. Fifth assessment report. Cambridge University Press, Cambridge, UK. Jevrejeva S., Jackson L.P., Riva R.E.M., Grinsted A., Moore J.C., 2016. Coastal sea level rise with warming above 2°C. Proceedings of the National Academy of Sciences, 113, 13342-13347. Doi: 10.1073/pnas.1605312113. Junk W.J., AN S., Finlayson C.M., Gopal B., Kvet J., Mitchell S.A., Mitsch W.J., Robarts R.D., 2013. Current state of knowledge regarding the world’s wetlands and their future under global climate change: A synthesis. Aquatic Science, 75, 151-167. Doi: 10.1007/s00027-012-0278-z. Jordan A., Rayner T., Schroeder H., Adger N., Anderson K., Bows A., Le Quéré C., Joshi M., Mander S., Vaughan N., Whitmarsh L., 2013. Going beyond two degrees? The risks and opportunities of alternative options. Climate Policy, 13, 751-769. Doi: 10.1080/14693062.2013.835705. Kelly P.M., Adger W.N., 2000. Theory and practice in assessing vulnerability to climate change and facilitating adaptation. Climatic Change, 47, 325-352. Doi: 10.1023/A:1005627828199. Kirwan M.L., Megonigal J.P., 2013. Tidal wetland stability in the face of human impacts and sea-level rice. Nature, 504, 53-60. Doi: 10.1038/nature12856. Koerth J., Vafeidis A.T., Hinkel J., Sterr H., 2013. What motivates coastal households to adapt pro actively to sea-level rise and increased flood risk? Regional Environmental Change, 13, 879-909. Doi: 10.1007/s10113-12-399-x. Kontgis K., Schneider A., Fox J;,Saksena S., Spencer J.H., Castrence M., 2014. Monitoring peri urbanization in the greater Ho Chi Minh City metropolitan area. Applied Geography, 53, 377-388. Doi: 10.1016/j.apgeogr.2014.06.029. Kopp R.E., Horton R.M., Little C.M., Mitrovica J.X., Oppenheimer M., Rasmussen D.J., Strauss B.H., Tebaldi C., 2014. Probabilistic 21st and 22nd century sea-level projections at a global network of tide-gauge sites. Earth’s Future, 2, 383-406. Doi: 10.1002/2014EF000239. Kuenzer C., Bluemel A., Gebhardt S., Quoc T., Dech S., 2011. Remote sensing of mangrove ecosystems:  A review.Remote Sensing, 3, 878-928. Doi: 10.3390/rs3050878. Lacerda G.B.M., Silva C., Pimenteira C.A.P., Kopp Jr. R.V., Grumback R., Rosa L.P., de Freitas M.A.V., 2013. Guidelines for the strategic management of flood risks in industrial plant oil in the Brazilian coast: Adaptive measures to the impacts of sea level rise. Mitigation and Adaptation Strategies for Global Change, 19, 104-1062. Doi: 10.1007/s11027-013-09459-x. Lam Dao Nguyen, Pham Van Bach, Nguyen Thanh Minh, Pham Thi Mai Thy, Hoang Phi Hung, 2011. Change detection of land use and river bank in Mekong Delta, Vietnam using time series remotely sensed data. Journal of Resources and Ecology, 2, 370-374. Doi: 10.3969/j.issn.1674-764x.2011.04.011. Lang N.T., Ky B.X., Kobayashi H., Buu B.C., 2004. Development of salt tolerant varieties in the Mekong delta. JIRCAS Project, Can Tho University, Can Tho, Vietnam, 152. Le Cozannet G., Rohmer J., Cazenave A., Idier D., Van de Wal R., de Winter R., Pedreros R., Balouin Y., Vinchon C., Oliveros C., 2015. Evaluating uncertainties of future marine flooding occurrence as sea-level rises. Environmental Modelling and Software, 73, 44-56. Doi: 10.1016/j.envsoft.2015.07.021. Le Cozannet G., Manceau J.-C., Rohmer J., 2017. Bounding probabilistic sea-level projections with the framework of the possible theory. Environmental Letters Research, 12, 12-14. Doi.org/10.1088/1748-9326/aa5528.Chikamoto Y., 2014. Recent Walker circulation strengthening and Pacific cooling amplified by Atlantic warming. Nature Climate Change, 4, 888-892. Doi: 10.1038/nclimate2330. Lovelock C.E., Cahoon D.R., Friess D.A., Gutenspergen G.R., Krauss K.W., Reef R., Rogers K., Saunders M.L., Sidik F., Swales A., Saintilan N., Le Xuan Tuyen, Tran Triet, 2015. The vulnerability of Indo-Pacific mangrove forests to sea-level rise. Nature, 526, 559-563. Doi: 10.1038/nature15538. MA Millennium Ecosystem Assessment, 2005. Ecosystems and human well-being: Current state and trends. Island Press, Washington DC, 266p. Masterson J.P., Fienen M.N., Thieler E.R., Gesch D.B., Gutierrez B.T., Plant N.G., 2014. Effects of sea level rise on barrier island groundwater system dynamics - ecohydrological implications. Ecohydrology, 7, 1064-1071. Doi: 10.1002/eco.1442. McGanahan G., Balk D., Anderson B., 2007. The rising tide: Assessing the risks of climate changes and human settlements in low elevation coastal zones.Environment and urbanization, 19, 17-37. Doi: 10.1177/095624780707960. McIvor A., Möller I., Spencer T., Spalding M., 2012. Reduction of wind and swell waves by mangroves. The Nature Conservancy and Wetlands International, 1-27. Merryn T., Pidgeon N., Whitmarsh L., Ballenger R., 2016. Expert judgements of sea-level rise at the local scale. Journal of Risk Research, 19, 664-685. Doi.org/10.1080/13669877.2015.1043568. Monioudi I.N., Velegrakis A.F., Chatzipavlis A.E., Rigos A., Karambas T., Vousdoukas M.I., Hasiotis T., Koukourouvli N., Peduzzi P., Manoutsoglou E., Poulos S.E., Collins M.B., 2017. Assessment of island beach erosion due to sea level rise: The case of the Aegean archipelago (Eastern Mediterranean). Nat. Hazards Earth Syst. Sci., 17, 449-466. Doi: 10.5194/nhess-17-449-2017. MONRE - Ministry of Natural Resources and Environment, 2016. Scenarios of climate change and sea level rise for Vietnam. Publishing House of Environmental Resources and Maps Vietnam, Hanoi, 188p. Montz B.E., Tobin G.A., Hagelman III R.R., 2017. Natural hazards. Explanation and integration. The Guilford Press, NY, 445p. Morgan L.K., Werner A.D., 2014. Water intrusion vulnerability for freshwater lenses near islands. Journal of Hydrology, 508, 322-327. Doi: 10.1016/j.jhydrol.2013.11.002. Muis S., Güneralp B., Jongman B., Aerts J.C.H.J., Ward P.J., 2015. Science of the Total Environment, 538, 445-457. Doi: 10.1016/j.scitotenv.2015.08.068. Murray N.J., Clemens R.S., Phinn S.R., Possingham H.P., Fuller R.A., 2014. Tracking the rapid loss of tidal wetlands in the Yellow Sea. Frontiers in Ecology and Environment, 12, 267-272. Doi: 10.1890/130260. Neumann B., Vafeidis A.T., Zimmermann J., Nicholls R.J., 2015a. Future coastal population growth and exposure to sea-level rise and coastal flooding. A global assessment. Plos One, 10, 1-22. Doi: 10.1371/journal.pone.0118571. Nguyen A. Duoc, Savenije H. H., 2006. Salt intrusion in multi-channel estuaries: a case study in the Mekong Delta, Vietnam. Hydrology and Earth System Sciences Discussions, European Geosciences Union, 10, 743-754. Doi: 10.5194/hess-10-743-2006. Nguyen An Thinh, Nguyen Ngoc Thanh, Luong Thi Tuyen, Luc Hens, 2017. Tourism and beach erosion: Valuing the damage of beach erosion for tourism in the Hoi An, World Heritage site. Journal of Environment, Development and Sustainability. Nguyen An Thinh, Luc Hens (Eds.), 2018. Human ecology of climate change associated disasters in Vietnam: Risks for nature and humans in lowland and upland areas. Springer Verlag, Berlin.Nguyen An Thinh, Vu Anh Dung, Vu Van Phai, Nguyen Ngoc Thanh, Pham Minh Tam, Nguyen Thi Thuy Hang, Le Trinh Hai, Nguyen Viet Thanh, Hoang Khac Lich, Vu Duc Thanh, Nguyen Song Tung, Luong Thi Tuyen, Trinh Phuong Ngoc, Luc Hens, 2017. Human ecological effects of tropical storms in the coastal area of Ky Anh (Ha Tinh, Vietnam). Environ Dev Sustain, 19, 745-767. Doi: 10.1007/s/10668-016-9761-3. Nguyen Van Hoang, 2017. Potential for desalinization of brackish groundwater aquifer under a background of rising sea level via salt-intrusion prevention river gates in the coastal area of the Red River delta, Vietnam. Environment, Development and Sustainability. Nguyen Tho, Vromant N., Nguyen Thanh Hung, Hens L., 2008. Soil salinity and sodicity in a shrimp farming coastal area of the Mekong Delta, Vietnam. Environmental Geology, 54, 1739-1746.  Doi: 10.1007/s00254-007-0951-z. Nguyen Thang T.X., Woodroffe C.D., 2016. Assessing relative vulnerability to sea-level rise in the western part of the Mekong River delta. Sustainability Science, 11, 645-659. Doi: 10.1007/s11625-015-0336-2. Nicholls N.N., Hoozemans F.M.J., Marchand M., Analyzing flood risk and wetland losses due to the global sea-level rise:  Regional and global analyses.Global Environmental Change, 9, S69-S87. Doi: 10.1016/s0959-3780(99)00019-9. Phan Minh Thu, 2006. Application of remote sensing and GIS tools for recognizing changes of mangrove forests in Ca Mau province. In Proceedings of the International Symposium on Geoinformatics for Spatial Infrastructure Development in Earth and Allied Sciences, Ho Chi Minh City, Vietnam, 9-11 November, 1-17. Reise K., 2017. Facing the third dimension in coastal flatlands.Global sea level rise and the need for coastal transformations. Gaia, 26, 89-93. Renaud F.G., Le Thi Thu Huong, Lindener C., Vo Thi Guong, Sebesvari Z., 2015. Resilience and shifts in agro-ecosystems facing increasing sea-level rise and salinity intrusion in Ben Tre province, Mekong Delta. Climatic Change, 133, 69-84. Doi: 10.1007/s10584-014-1113-4. Serra P., Pons X., Sauri D., 2008. Land cover and land use in a Mediterranean landscape. Applied Geography, 28, 189-209. Shearman P., Bryan J., Walsh J.P., 2013.Trends in deltaic change over three decades in the Asia-Pacific Region. Journal of Coastal Research, 29, 1169-1183. Doi: 10.2112/JCOASTRES-D-12-00120.1. SIWRR-Southern Institute of Water Resources Research, 2016. Annual Report. Ministry of Agriculture and Rural Development, Ho Chi Minh City, 1-19. Slangen A.B.A., Katsman C.A., Van de Wal R.S.W., Vermeersen L.L.A., Riva R.E.M., 2012. Towards regional projections of twenty-first century sea-level change based on IPCC RES scenarios. Climate Dynamics, 38, 1191-1209. Doi: 10.1007/s00382-011-1057-6. Spencer T., Schuerch M., Nicholls R.J., Hinkel J., Lincke D., Vafeidis A.T., Reef R., McFadden L., Brown S., 2016. Global coastal wetland change under sea-level rise and related stresses: The DIVA wetland change model. Global  and Planetary Change, 139, 15-30. Doi:10.1016/j.gloplacha.2015.12.018. Stammer D., Cazenave A., Ponte R.M., Tamisiea M.E., 2013. Causes of contemporary regional sea level changes. Annual Review of Marine Science, 5, 21-46. Doi: 10.1146/annurev-marine-121211-172406. Tett P., Mee L., 2015. Scenarios explored with Delphi. In: Coastal zones ecosystems services. Eds., Springer, Berlin, Germany, 127-144. Tran Hong Hanh, 2017. Land use dynamics, its drivers and consequences in the Ca Mau province, Mekong delta, Vietnam. PhD dissertation, 191p. VUBPRESS Brussels University Press, ISBN 9789057186226, Brussels, Belgium. Tran Thuc, Nguyen Van Thang, Huynh Thi Lan Huong, Mai Van Khiem, Nguyen Xuan Hien, Doan Ha Phong, 2016. Climate change and sea level rise scenarios for Vietnam. Ministry of Natural resources and Environment. Hanoi, Vietnam. Tran Hong Hanh, Tran Thuc, Kervyn M., 2015. Dynamics of land cover/land use changes in the Mekong Delta, 1973-2011: A remote sensing analysis of the Tran Van Thoi District, Ca Mau province, Vietnam. Remote Sensing, 7, 2899-2925. Doi: 10.1007/s00254-007-0951-z Van Lavieren H., Spalding M., Alongi D., Kainuma M., Clüsener-Godt M., Adeel Z., 2012. Securing the future of Mangroves. The United Nations University, Okinawa, Japan, 53, 1-56. Water Resources Directorate. Ministry of Agriculture and Rural Development, 2016. Available online: http://www.tongcucthuyloi.gov.vn/Tin-tuc-Su-kien/Tin-tuc-su-kien-tong-hop/catid/12/item/2670/xam-nhap-man-vung-dong-bang-song-cuu-long--2015---2016---han-han-o-mien-trung--tay-nguyen-va-giai-phap-khac-phuc. Last accessed on: 30/9/2016. Webster P.J., Holland G.J., Curry J.A., Chang H.-R., 2005. Changes in tropical cyclone number, duration, and intensity in a warming environment. Science, 309, 1844-1846. Doi: 10.1126/science.1116448. Were K.O., Dick O.B., Singh B.R., 2013. Remotely sensing the spatial and temporal land cover changes in Eastern Mau forest reserve and Lake Nakuru drainage Basin, Kenya. Applied Geography, 41, 75-86. Williams G.A., Helmuth B., Russel B.D., Dong W.-Y., Thiyagarajan V., Seuront L., 2016. Meeting the climate change challenge: Pressing issues in southern China an SE Asian coastal ecosystems. Regional Studies in Marine Science, 8, 373-381. Doi: 10.1016/j.rsma.2016.07.002. Woodroffe C.D., Rogers K., McKee K.L., Lovdelock C.E., Mendelssohn I.A., Saintilan N., 2016. Mangrove sedimentation and response to relative sea-level rise. Annual Review of Marine Science, 8, 243-266. Doi: 10.1146/annurev-marine-122414-034025.